Sustainable Knowledge Plasticity as a Key Mediator of Organizational Performance in Indonesian FMCG Distribution Firms - Lala Setiany Wee; David Sukardi Kodrat; Damelina Basauli Tambuna (Politeknik Siber Cerdika Internasional, 2026)
Background: There are rapid environmental changes in the FMCG distribution industry in Indonesia; this steady change demands constant adaptation by organizations and renewal of knowledge. Existing research investigates organizational agility, thriving at work, and knowledge management independently, with no prior study examining the integrated impact of these variables on sustainable performance. This study conceptualizes Sustainable Knowledge Plasticity (SKP) as a novel dynamic capability that enables organizations to engage in continuous cycles of knowledge renewal and integration. Objective: This study aims to explore the mediating role of Sustainable Knowledge Plasticity (SKP) between organizational agility, thriving at work, and knowledge management in predicting organizational performance. Methods: This study employed a quantitative cross-sectional design using stratified purposive sampling among 385 FMCG distribution employees across Java and Sulawesi provinces. Data were collected using a validated Likert-scale questionnaire, followed by analysis through SEM-PLS (SmartPLS 4.0). Results: Organizational agility, thriving at work, and knowledge management have significant effects on Sustainable Knowledge Plasticity (SKP), which in turn directly influences organizational performance. The mediation analysis indicates that Sustainable Knowledge Plasticity (SKP) is a critical mechanism for translating adaptive capacities into sustainable outcomes. Conclusion: Sustainable Knowledge Plasticity (SKP) is an essential precursor to organizational performance, linking adaptability with sustainability in the long term and extending Dynamic Capability Theory through a strong emphasis on continual knowledge replenishment.